Gender-based analysis of factors contributing to post-vacation blues: A case study of young generation tourists in West Java - Sukriah, Erry; Putri Fadillah, Shakira Mauludy; Pratama, Armandha Redo (Universitas Pendidikan Indonesia, 2025)
AbstrakThis study aims to analyze the factors contributing to the symptoms of post-vacation blues based on gender among domestic travelers in Java. This phenomenon refers to a psychological condition characterized by feelings of sadness, loss of motivation, and difficulty readjusting to daily routines after returning from a vacation. In dealing with daily routines, tourists also experience difficulties in managing time, especially sleep and rest time, decreased focus on work, and slowed speed in carrying out daily tasks. The research employs a quantitative approach and utilizes Exploratory Factor Analysis (EFA), involving 250 respondents residing in Java. The results of the analysis reveal significant differences between genders. For male tourists, the primary factors identified are memorable trip, mental pressure, body condition, emotional ties, and travel fatigue. In contrast, among female tourists, in addition to the five aforementioned factors, there is also the factor of emotional response, which indicates emotional sensitivity and complex expectations, as well as money matters related to financial issues. This finding suggests that female travelers are more vulnerable to experiencing post-vacation blues.AbstrakPenelitian ini bertujuan untuk menganalisis faktor-faktor yang menjadi gejala terjadinya post-vacation blues berdasarkan gender pada kalangan domestik di Pulau Jawa. Fenomena ini merujuk pada kondisi psikologis yang ditandai dengan perasaan sedih, kehilangan motivasi, dan kesulitan beradaptasi kembali ke rutinitas sehari-hari setelah berlibur. Dalam menghadapi rutinitas sehari-hari, wisatawan juga mengalami kesulitan mengatur waktu terutama waktu tidur dan istirahat, turunnya fokus pada pekerjaan, serta kecepatan mengerjakan tugas sehari-hari yang melambat. Penelitian ini menggunakan pendekatan kuantitatif dan teknik analisis Exploratory Factor Analysis (EFA) dengan melibatkan 250 responden yang berdomisili di Pulau Jawa. Hasil analisis menunjukan adanya perbedaan signifikan pada gender yang berbeda. Pada wisatawan laki-laki faktor utama yang menentukan ialah memorable trip, mental pressure, body condition, emotional ties, dan travel fatigue. Sedangkan pada wisatawan perempuan selain 5 faktor sebelumnya juga terdapat faktor emotional response yang menunjukan sensitivitas emosional dan ekspektasi yang kompleks, serta money mater yang berkaitan dengan masalah keuangan.Hal ini menunjukan bahwa wisatawan wanita akan lebih rentan mengalami post vacation blues.